2013
DOI: 10.3892/ijo.2013.2003
|View full text |Cite
|
Sign up to set email alerts
|

Let-7g and miR-21 expression in non-small cell lung cancer: Correlation with clinicopathological and molecular features

Abstract: Abstract. MicroRNAs (miRNAs) play a key role in cancer pathogenesis and are involved in several human cancers, including non-small cell lung cancer (NSCLC). This study evaluated Let-7g and miR-21 expression by quantitative realtime PCR in 80 NSCLC patients and correlated the results with their main clinicopathological and molecular features. MiR-21 expression was significantly higher in NSCLC tissues compared to non-cancer lung tissues (p<0.0001), while no significant changes in Let-7g expression were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 46 publications
3
34
0
1
Order By: Relevance
“…Among ras oncogenes, K-ras had the greatest impact on human cancers. Highly expressed miR-21 in lung cancer tissues has been associated with K-ras mutations and been suggested as a tumor marker of lung cancer in clinical applications (Capodanno et al, 2013). Our study showed that miR-21 antisense expression in TE-13 cells can cause decreased expression of K-ras protein, suggesting that downregulation of miR-21 expression can inhibit K-ras gene expression.…”
Section: Discussionmentioning
confidence: 55%
“…Among ras oncogenes, K-ras had the greatest impact on human cancers. Highly expressed miR-21 in lung cancer tissues has been associated with K-ras mutations and been suggested as a tumor marker of lung cancer in clinical applications (Capodanno et al, 2013). Our study showed that miR-21 antisense expression in TE-13 cells can cause decreased expression of K-ras protein, suggesting that downregulation of miR-21 expression can inhibit K-ras gene expression.…”
Section: Discussionmentioning
confidence: 55%
“…These data suggest that genistein may be a potential targeting drug for human lung cancer. The occurrence and development of lung cancer is a complex, multiple links process, including the oncogene activation and mutations or deficiency of tumor suppressor genes, in the process of the occurrence and metastasis of lung carcinoma, genetic variation is the extensive research focus for many years (20). miRNA widely exists in human chromosomes, and it have very strong organization specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro and in vivo studies have indicated that miR-21 is frequently overexpressed in various human tumors and in cancer cell lines, and promotes oncogenesis, suggesting that it is an onco-miR (27,28). Additionally, the association between miR-21 and drug resistance has been investigated and high levels of miR-21 were detected in 5-fluorouracil-resistant human pancreatic, cisplatin-resistant ovarian, doxorubicin-resistant breast and cisplatin-resistant neuroblastoma cancer cells (15,(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%